'The body is a battleground for unwanted and unexpressed emotions': exploring eating disorders and the role of emotional intelligence. Issue 3 (4th May 2019) - Foye, Una; Hazlett, Diane E.; Irving, Pauline
ABSTRACT: Emotional difficulties have been observed in individuals with eating disorders across awide range of studies, including poor interoceptive awareness, confusion of emotional states and difficulties with emotional language. Literature has linked these difficulties with emotional functioning as being an important factor related to the core aetiology ofeating disorders, however limited knowledge exists to how this impacts on professionalability to engage patients within treatment as a result of such dysfunction. Using aqualitative design this paper explores how facets of Emotional intelligence (EI) are related to the experience of an eating disorder. The study sampled a total of 32 participants with either a professional background working with eating disorders (n=27)or participants with personal lived experience (n=5), with a number of the participants (n=13) identified as having dual roles. The findings of the study show that aspects of EIsuch as emotional regulation and lack of an emotional language are considered to beat the core of the onset and maintenance of these disorders. Additional aspects of emotional awareness and expression were found to be related to treatment disengagement and difficulties. Building on previous literature, this paper found suchemotional deficits as a transdiagnostic issue rather than specifically anorexia nervosa. Furthermore, such dysfunction was seen by professionals to have a considerable impact on therapeutic relationships and successful treatment. These findings provide insight into the potential applications that EI may have in addressing aspects of theeating disorder to create better outcomes for treatment and intervention models.